THE EFFECTS OF CHANGING MEASUREMENT INTERVALS AND CUFFS ON BLOOD PRESSURE MONITOR VALIDATION. (April 2021) - Lewis, Philip; Smith, Lara Jane; Budd, Jayne; Curtis, Janet; Wilkinson, Helen; Adeyoju, Joshua; Adeyoju, Daniel Adedeji; Woodyatt, Wiesia Krystyna; Rajai, Azita
Abstract : Objective: We investigated whether intervals between automated BP measurements (AutoBPMs) and alternating manual BP measurements (ManBPMs) might affect validation protocol results and if cuff changes had independent affects. Design and method: The BP of 72 healthy volunteers (59 female, 13 male; age 36–58 years; BMI 23–29 Kg/m2), SBP 90–180 mmHg, was measured manually by trained observers using an Accoson mercury sphygmomanometer alternating with automated readings with an Omron M6 AC monitor in 2 phases. In Phase 1, participants were randomised to 9 BPMs (ManBPMs with a Standard Adult Accoson cuff alternating with AutoBPMs with an Omron RML31 D-ring cuff) at 30 second intervals followed by 9 BPMs at 60 second intervals or vice versa. In Phase 2, participants were randomised to 9 alternating ManBPMs and AutoBPMs at 60 second intervals using an Omron RML31 cuff for all, followed by 9 alternating ManBPMs and AutoBPMs using an equivalent sized D-ring cuff made with Accoson Standard cuff materials for all or vice versa. Statistical analyses were made using RStudio with Mixed Model Repeated Measure (MMRM) modelling. Results: Phase 1 ManSBPs were significantly greater than AutoSBPs especially at 30 second intervals (ManSBP – AutoSBP = 2.76 mmHg [CI1.5, 4.01]) than at 60 second intervals (-0.92 [-0.58, 2.42]). ManDBPs were lower than AutoDBPs at 60 second intervals (-3.25 [-4.53, -1.97]) than at 30 second intervals (-1.19 [-2.17, -0.21]) 1.5, 4.01]) In Phase 2, AutoDBPs were lower than ManDBPs but AutoSBPs were not significantly different from ManSBPs. These results were unaffected by using either cuff. There was no significant difference if ABPMs were compared with the mean of the preceding and subsequent readings or with the value of the preceding or subsequent readings nearest to the ABPM value. Comparisons were unaffected by excluding the first 2 of the 9 alternating BPMs at each stage Figure. No caption available. Conclusions: Intervals between alternating manual and automated BPMs used in validation protocols may significantly affect the outcome of a validation unrelated to the cuff used. SBP differences are greater at 30 second intervals than at 60 second intervals whilst DBP differences are greater at 60 seconds.